The Specific Dermatoses of Pregnancy - Polańska, Paulina (Quality in Sport, 2025)
Introduction and purpose: Pregnancy-specific dermatoses are a group of pruritic skin disorders that arise exclusively during pregnancy or the postpartum period. They encompass four primary conditions: atopic eruption of pregnancy (AEP), polymorphic eruption of pregnancy (PEP), intrahepatic cholestasis of pregnancy (ICP), and pemphigoid gestationis (PG). This review aims to provide a comprehensive analysis of their prevalence, clinical characteristics, underlying mechanisms, therapeutic strategies, and potential fetal risks. Results: These dermatoses often present with overlapping clinical features, making accurate differential diagnosis crucial. While some pose minimal risk to the fetus, others, such as ICP and PG, are associated with significant complications, including preterm birth and stillbirth. The underlying pathophysiology remains incompletely understood, with hormonal, immunological, genetic, and environmental factors playing key roles. Treatment strategies focus primarily on symptomatic relief, with topical corticosteroids and oral antihistamines being the mainstay of therapy, while ursodeoxycholic acid is the treatment of choice for ICP. Conclusions: A multidisciplinary approach is essential for optimal maternal and fetal outcomes. Further research is needed to better understand the mechanisms and develop more effective treatment options for these conditions.